2013
DOI: 10.2478/s11535-013-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the extraction solvent on antioxidant activity of Althaea officinalis L. root extracts

Abstract: Althaea officinalis (Malvaceae) is a well-known plant that is widely distributed throughout the world. Aqueous and hydroalcoholic extracts from A. officinalis root are used mainly because of their antitussive and expectorant activity. It is well known that these activities are based on the polysaccharide composition, but little is known about the possible antioxidant activity of root extract. The present study evaluated antioxidant activity of root extracts prepared with different extraction solvents applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…We found an inhibition of H 2 O 2 -mediated decrease of the viability, when M were pre-treated with Phytohustil R . Our findings are congruent with publications of others (Sadighara et al, 2012;Benbassat et al, 2014) showing that Phytohustil R and REAo have antioxidant properties, stimulate anti-oxidative defense mechanisms and, thus, may protect against intracellular ROS increase, i.e., oxidative stress in M . In contrast to non-mucosal tissues, the mucosal tissues have close contact with numerous and diverse commensal microorganisms, as well as pathogens, which can trigger pro-inflammatory responses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found an inhibition of H 2 O 2 -mediated decrease of the viability, when M were pre-treated with Phytohustil R . Our findings are congruent with publications of others (Sadighara et al, 2012;Benbassat et al, 2014) showing that Phytohustil R and REAo have antioxidant properties, stimulate anti-oxidative defense mechanisms and, thus, may protect against intracellular ROS increase, i.e., oxidative stress in M . In contrast to non-mucosal tissues, the mucosal tissues have close contact with numerous and diverse commensal microorganisms, as well as pathogens, which can trigger pro-inflammatory responses.…”
Section: Discussionsupporting
confidence: 93%
“…Marshmallow is well-known for its healing properties since ancient time. It has been reported that a water extract from roots of A. officinalis had stimulating effects on cell viability and proliferation of epithelial cells, but not on primary fibroblasts (Deters et al, 2010;Benbassat et al, 2014). We now found that Phytohustil R increased the viability of M , key components of the innate immune defense system, without revealing cytotoxic effects.…”
Section: Discussionmentioning
confidence: 43%
“…[ 12 ] Investigation about cytotoxic activity and safety of extract showed that the liquid extracts had no significant cytotoxicity on human cells. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the antioxidant activity of A. officinalis root extracts by water as solvent showed no antioxidant activity, while extracts by ethanol water (50: 50, 70: 30) had a higher antioxidant effect than that of ethanol:water (90: 10). There is a positive correlation between its phenolic and flavonoid contents and the antioxidant activities of A. officinalis [37]. Reduction in free radical oxygen in the respiratory system is associated with inflammation and irritation, which can reduce the reason for cough.…”
Section: Antimicrobial Activities Of a Officinalismentioning
confidence: 99%